ASPEK HUKUM TERHADAP TINDAK PIDANA PENCUCIAN UANG DENGAN MODUS SMURFING - Faiz, Agil; Yusrizal, Yusrizal; Iskandar, Hadi (Jurnal Ilmiah Mahasiswa Fakultas Hukum Universitas Malikussaleh, 2024)
The objective of this study is to explore the legal dimensions of the criminal offense of money laundering, specifically focusing on the smurfing technique. Additionally, it seeks to examine the evidentiary framework applicable to the crime of money laundering as defined by Act No. 8 of 2010 concerning the Penal Procedure for Money Laundering. The advancement of technology has introduced various innovative methods in the prosecution of money laundering, one of which is the smurfing technique. This method involves the placement of illicitly obtained funds into the financial system by dividing the money into smaller sums and depositing them into bank accounts to evade detection. The concept of smurfing gained prominence following Judgment No. 62/Pid.Sus/2021/PN Jkt.Utr, which referenced "smurfing" as a tactic employed by criminals to obscure the origins of their illicit gains, thus rendering it a significant subject of analysis under Act No. 8 of 2010. This research employs a normative jurisprudence methodology, utilizing both qualitative and legislative approaches. The findings indicate that while the smurfing technique is not explicitly defined in Act No. 8 of 2010, its operational phases”ranging from initial funding to distribution and eventual withdrawal”align with the stipulations outlined in Articles 3, Articles 4, and Articles 5 of the Penal Enforcement Act on Money Laundering.